The lack of listening: News sources in South Africa's five general elections, 1994–2014. (August 2019) - Jones, Bernadine
With most political journalism research focusing on Western elections, one tends to forget that mediatization exists in non-Western reportage too. Television news is still a powerful political tool, especially in developing democracies and particularly in South Africa – the case of this research. This article investigates the sources used on television news during five democratic South African elections, 1994–2014, and aims to shed light on the type of mediatized political reporting in and about a non-Western country. The main finding of this research is that news sources during the South African elections were made up increasingly of pundits and decreasingly of political leaders and citizens. The importance of 'listening' directly cannot be overstated, especially in developing democracies like South Africa. A solid link between journalist and politician as well as journalist and citizen is crucial to implement substantive information necessary to enable the media's democratic duty. When journalists ignore citizen voices in favor of interpretive and evaluative sources, this link is steadily degraded. This article suggests reasons for the drop-off of political and citizen sources in South African election reporting, and, on the eve of the sixth general election in May 2019, argues a case for more 'straight from source' voices in political journalism.